Production and quality of okra produced with mineral and organic fertilization - Santos, Hemmannuella C. (2019)
Okra, Abelmoschus esculentus (L.) Moench, is a vegetable with annual fruit native to hot regions of Africa, well adapted to the conditions of the Northeast and Southeast regions of Brazil, where it is widely used by small farmers. This study aimed to evaluate the effect of mineral and organic fertilization on the production and quality of okra fruits. The experiment was conducted in randomized block design, with three replicates and eleven treatments defined according to a Baconian matrix. Treatments consisted of doses of N (0, 100, 200 and 300 kg ha(-1)), P (0, 100, 200 and 300 kg ha(-1)) and K (0, 80, 160 and 240 kg ha(-1)), as well as absence and presence of organic compost (30 t ha(-1)). The following parameters were evaluated: plant height, stem diameter, number of leaves, production of fruits plant(-1), number of fruits plant(-1), fruit length and diameter and fruit quality (pH, soluble solids, titratable acidity, vitamin C and electrical conductivity). The crop is demanding in terms of K and N fertilizations, with increments of 15.8 and 36% in the mean number and diameter of fruits, respectively. Organic fertilization did not influence the vegetative growth of okra, but was beneficial to the production of fruits with higher vitamin C content, 52% higher than the contents found in fruits produced without such input.